2009
DOI: 10.1007/s00586-009-1198-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and complications in flaccid neuromuscular scoliosis (Duchenne muscular dystrophy and spinal muscular atrophy) with posterior-only pedicle screw instrumentation

Abstract: Literature has described treatment of flaccid neuromuscular scoliosis using different instrumentation; however, only one article has been published using posterior-only pedicle screw fixation. Complications using pedicle screws in paralytic neuromuscular scoliosis has not been described before. To present results and complications with posterior-only pedicle screws, a retrospective study was carried out in 27 consecutive patients with flaccid neuromuscular scoliosis (Duchenne muscular dystrophy and spinal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 48 publications
(75 reference statements)
1
42
1
Order By: Relevance
“…During the early stages of pedicle screw use, there was evidence that their technical difficulty to insert, especially into osteopenic bone, led to higher rates of complications compared to a sublaminar alone system (60).…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early stages of pedicle screw use, there was evidence that their technical difficulty to insert, especially into osteopenic bone, led to higher rates of complications compared to a sublaminar alone system (60).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…This led to the development of the hybrid method using both techniques which showed improved outcomes (60,61).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…They concluded that the cause of the hemothorax was breaching of the lateral wall of the pedicle or the anterior vertebral body cortex during pedicle screw probing or insertion. 10 Pang et al reported a hemothorax caused by a Gelpi retractor during posterior surgery for adolescent idiopathic scoliosis. 14 In the present case, a postoperative CT scan confirmed a hematoma of the left paravertebral muscle at the T-11 level, which is the skin entry point of the trocar tip.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the recent trend to treat neuromuscular scoliosis patients with pedicle screws instrumentation through a posterior-only approach, the use of screws instead of smooth rods to anchor the ilium is increasingly documented in the literature [32,33,67,68]. It offers the theoretical advantage of diminishing implant pullout or cutout associated with a smooth rods inserted in the iliac wings.…”
Section: Iliac Screwsmentioning
confidence: 99%
“…Most authors report this technique for the treatment of neuromuscular scoliosis in pediatric patients without additional sacral fixation. Proximal spinal anchorage is done with sublaminar wires [67,71] or with pedicle screws from the L5 level [32,33,72].…”
Section: Iliac Screwsmentioning
confidence: 99%